Laparoscopic findings in women with symptomatic endometriosis - Gurreonero Briceño, Edgar (2015)
Objectives: To correlate clinical characteristics and surgical findings in patients subjected to laparoscopic surgery for pelvic endometriosis. Design: Analytical, comparative, retrospective, horizontal study. Setting: Hospital Alberto Sabogal Sologuren, EsSalud, Callao, Peru. Participants: Women with pelvic endometriosis. Interventions: Between January 2005 and December 2009 1 616 gynecological surgical laparoscopies were performed. In order to correlate clinical characteristics with surgical findings, data was processed in Excel for Windows, SPSS statistical version 14.0 and chi square; confidence interval was 95%. Main outcome measures: Correlation of clinical characteristics and operative findings. Results: From 1 616 gynecological laparoscopies endometriosis was found in 24,4% (394 cases); higher incidence was observed in 2009 (26,4% of all cases). Average age was 37,1 ± 1,9 years and symptoms or abnormalities most frequently found were infertility (42,9%), pelvic pain (14,3%), pelvic tumor (4,1%), uterine bleeding (2%), and abdominal pain (2%). Stages I (46%) and II (26%) were most frequent. Usual affected structures were uterus (76,4%), uterosacral ligaments (42,9%) and Douglas cul-de-sac (42,1%). Endometriotic lesions affected also extragenital structures, such as bladder wall (15%) and rectum and sigmoid colon (4,3%). There was no relation between infertility and lesion localization. Pelvic pain was associated to endometriotic lesions in the left tube and uterosacral ligaments. Infertility did not significantly correlate with staging (p = 0,068) and pelvic pain did not increase with higher stage of the disease (p = 0,912). Conclusions: There existed correlation between uterine and uterosacral ligaments endometriotic lesions localization and presence of chronic pelvic pain. Infertility did not correlate with any particular localization. There was no correlation between clinical manifestations and lesions staging.